2018
DOI: 10.1177/1359105318790052
|View full text |Cite
|
Sign up to set email alerts
|

Netherton syndrome; neuropsychological and psychosocial functioning of child and adult patients and their parents

Abstract: Compared with normative data, Netherton syndrome patients showed neuropsychological and psychosocial problems. Standard follow-up is necessary to identify problems at early stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…This finding is associated with significant impairment of quality of life and sleep, overprotection by parents, stigmatization, and isolation. 3 In 2017, Paller et al 8 reported that several disorders of keratinization are defined by an IL-17-dominant immune profile, and Malik et al 10 reported that patients with NS had the highest induction of T H 17/IL-23 pathway genes. Targeted therapy has been tried with the anti-TNF agent infliximab in 2 adult patients with NS, resulting in cutaneous improvement.…”
Section: Key Pointsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is associated with significant impairment of quality of life and sleep, overprotection by parents, stigmatization, and isolation. 3 In 2017, Paller et al 8 reported that several disorders of keratinization are defined by an IL-17-dominant immune profile, and Malik et al 10 reported that patients with NS had the highest induction of T H 17/IL-23 pathway genes. Targeted therapy has been tried with the anti-TNF agent infliximab in 2 adult patients with NS, resulting in cutaneous improvement.…”
Section: Key Pointsmentioning
confidence: 99%
“…Skin infections are common, as are allergies, asthma, and increased levels of circulating eosinophils and total IgE . Affected individuals have lifelong ichthyosis lineariz circumflexa, associated with erythroderma, and pruritus . Treatment of NS is difficult, with the mainstay being bland emollients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, NS patients can show psychosocial and neuropsychological problems. Thus, in order to recognize these issues at an early phase, a standard follow-up is needed ( 86 ).…”
Section: Resultsmentioning
confidence: 99%
“…Quality of life was only reported in 5 studies ( 29 , 40 , 54 , 63 , 65 ). The strong focus on skin related problems combined with sparse attention for patients’ functioning as a person does not reflect the full range of impact that NS has on patient’s lives ( 75 ). Furthermore, side effects were infrequently reported, which may flatter treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%